2019
DOI: 10.1177/0142723719889240
|View full text |Cite
|
Sign up to set email alerts
|

Complex syntax and working memory in children with specific learning difficulties

Abstract: Working memory (WM) limitations are frequently reported for children with specific learning disorder (SLD). However, WM capacity influences more than literacy and numeracy, as research highlights the contribution of WM to language development, in particular syntax. In this article, the authors study the effect of syntactic intervention, i.e. syntactic elements intervening between filler and gap, on comprehension in children with SLD and evaluate the relationship of this effect to WM capacity. Specifically, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
(99 reference statements)
1
5
0
Order By: Relevance
“…One should note that a similar positive connection was discovered on the morpho-syntactic level of processing; it was shown that children with poor working memory were facing more significant syntactic difficulties (Stanford & Delage, 2020;Delage & Frauenfelder, 2020). To conclude, our analysis of existing papers led us to assuming the presence of a bi-directional connection between the development of vocabulary and executive functions, where working memory plays a special role in the growth of vocabulary.…”
Section: The Relationship Between Executive Functions and Languagesupporting
confidence: 56%
“…One should note that a similar positive connection was discovered on the morpho-syntactic level of processing; it was shown that children with poor working memory were facing more significant syntactic difficulties (Stanford & Delage, 2020;Delage & Frauenfelder, 2020). To conclude, our analysis of existing papers led us to assuming the presence of a bi-directional connection between the development of vocabulary and executive functions, where working memory plays a special role in the growth of vocabulary.…”
Section: The Relationship Between Executive Functions and Languagesupporting
confidence: 56%
“…Both monolingual and bilingual populations were included. The second group is composed by children with specific learning disorders (SLD), most of whom have dyslexia (Stanford & Delage, 2020). From the literature and also in their article in this issue, we learn that some of these children struggle with oral language problems.…”
Section: Some Notesmentioning
confidence: 99%
“…English question formation, possibly due to the computation involved, is a challenging area of development (e.g. Stanford & Delage, 2020). In contrast, Bangla-speaking young children did not have many errors in the formation of interrogative sentences, which could be attributed to the flexibility in the Bangla word order (Sultana, unpublished data).…”
mentioning
confidence: 99%